Basic principles and general approaches of development of industry of tourism are in Republic of Kazakhstan: tourist projects and approaches. (Journal of Economic Research & Business Administration, 2016)
Formation of market economy in Kazakhstan increased interest in formsand methods of tourist services. The development of the industry at an acceleratedpace and increase the negative effects of competition and commercializationof tourist activity has led to an understanding of the need for stateregulation of tourist business. Within a few generations, a significant part ofthe population of Kazakhstan used a travel service, resulting in the need forthem was the mass, ie, He came back to normal life, became part of the nationalculture. International tourism is currently one of the most dynamicallydeveloping branches of foreign economic activity. The steady growth of theimpact of tourism on the world economy as a whole and on the economiesof individual countries and regions is one of the most significant, permanentand long-term trends which accompanies the formation and development ofthe world economy. The tourism industry in the Republic of Kazakhstan onthe state level is recognized as one of the priority sectors of the economy.The implementation of the industrial-innovative development of Kazakhstan’seconomy leading role belongs to the system of local clusters. Қазақстандағы нарықтық экономиканы қалыптастыру нысандары мен әдістері туристік қызмет көрсету қызығушылығын күшейтті. Туристік бизнесті мемлекеттік реттеу туристік қызметті коммерциялизациялау және бәсекелестік салдарының теріс түсінігінің өсуіне және осы саланың қарқынмен дамуына әкелді. Бірнеше ұрпақтар халықтың едәуір бөлігі Қазақстанның туристік қызметімен тұтынды, соның нәтижесінде оларға қажеттілік болатын бұқаралық, яғни өмір нормасына ұлттық мәдениет бөлігі болып енді. Халықаралық туризм қазіргі уақытта ең серпінді дамып келе жатқан сыртқы экономикалық қызмет салаларының бірі болып табылады. Туризмнің ұдайы өсуіне тұтастай алғанда әлемдік экономиканы, жекелеген елдер экономикасы мен аймақтарын, аса маңызды тұрақты және ұзақ мерзімді үрдістердің, әлемдік шаруашылықтың құрылуы және дамуына толықтай ықпал етеді. Қазақстан Республикасындағы туризм индустриясы мемлекеттік деңгейінде басым экономика саласының бірі болып танылды. Қазақстанның экономиканы дамытудағы индустриялық- инновациялық ережелерін іске асырудағы жетекші рөлі отандық кластерлер жүйесінде атқарылады.
Keywords: MІСE – tourism; cultural tourism; farm tourism; the development of geoparks. MICE- туризм; мәдени- танымдық туризм; агроэкотуризм; геопрактердің дамуы.